Νanomaterial-Loaded Polymer Coating Prevents the In Vitro Growth of Candida albicans Biofilms on Silicone Biomaterials - Alexios Tsikopoulos; Konstantinos Tsikopoulos; Gabriele Meroni; Christoforos Gravalidis; Prodromos Soukouroglou; Athanasios Chatzimoschou; Lorenzo Drago; Stefanos Triaridis; Paraskevi Papaioannidou (MDPI AG, 2023)
Early failure of silicone voice prostheses resulting from fungal colonization and biofilm formation poses a major concern in modern ear nose throat surgery. Therefore, developing new infection prevention techniques to prolong those implants' survivorship is crucial. We designed an in vitro laboratory study to include nanomaterial-enhanced polymer coating with a plasma spraying technique against Candida albicans growth to address this issue. The anti-biofilm effects of high- and low-dose Al2O3 nanowire and TiO2 nanoparticle coatings were studied either alone or in conjunction with each other using checkerboard testing. It was demonstrated that both nanomaterials were capable of preventing fungal biofilm formation regardless of the anti-fungal agent concentration (median absorbance for high-dose Al2O3-enhanced polymer coating was 0.176 [IQR = 0.207] versus control absorbance of 0.805 [IQR = 0.381], p = 0.003 [98% biofilm reduction]; median absorbance for high-dose TiO2-enhanced polymer coating was 0.186 [IQR = 0.024] versus control absorbance of 0.766 [IQR = 0.458], p < 0.001 [93% biofilm reduction]). Furthermore, synergy was revealed when the Bliss model was applied. According to the findings of this work, it seems that simultaneous consideration of Al2O3 and TiO2 could further increase the existing antibiofilm potential of these nanomaterials and decrease the likelihood of localized toxicity.